The Vietnam provincial competitiveness index 2011 : - Malesky, Edmund (Vietnam Chamber of Commerce and Industry, 2011)
This seventh edition of the provincial competitiveness index presents the latest views of 6,922 Vietnamese enterprises on economic governance and the business enviroment across 63 province and cities. The report also analyzes the results of the second annuall survey of 1,970 foreign invested enterprises currently operating in Vietnam, providing an update on the performance and views of the existing foreign direct investment sector and the challenges Vietnam faces in attracting higher value-added investment and sustaining economic growth.